Hologram-based architecture for fan-in coupling in four-core fibers - Kaluza, Mateusz; Pogorzelec, Konrad; Lesiak, Piotr (Photonics Letters of Poland, 2025)
This study presents a fan-in coupler architecture for a four-core fiber, implemented using a single diffractive optical element (DOE). The DOE selectively excites two opposite cores while the remaining ones serve as receiving channels. The DOE was designed using an iterative algorithm, resulting in a computer-generated hologram and fabricated using two-photon polymerization (TPP). Numerical simulations and experimental measurements confirmed correct operation of the concept. The proposed coupler shows strong potential for applications in fiber-optic sensing and optical communications. Full Text: PDF References W. Chen et al., "Applications and Development of Multi-Core Optical Fibers", Photonics 11, 270 (2024). CrossRef J. Sun, W. Huang, A. Lorenz, M. Zeisberger, and M. A. Schmidt, "Tunable metafibers: remote spatial focus control using 3D nanoprinted holograms on dual-core fibers", Light Sci. Appl. 14, 237 (2025). CrossRef M. Khosravi, T. Wieduwilt, M. Zeisberger, A. Lorenz, and M.A. Schmidt, "Advanced remote focus control in multicore meta-fibers through 3D nanoprinted phase-only holograms", Nat. Commun. 16, 507 (2025). CrossRef C. Liu, L. Niu, K. Wang, and J. Liu, "3D-printed diffractive elements induced accelerating terahertz Airy beam", Opt. Express 24, 29342 (2016). CrossRef R.D. Muelas-Hurtado, J.L. Ealo, J.F. Pazos-Ospina, and K. Volke-Sepúlveda, "Generation of multiple vortex beam by means of active diffraction gratings", Appl. Phys. Lett. 112, 084101 (2018). CrossRef P. Komorowski, M. Kurowska, M. Kaluza, P. Czerwińska, P. Zagrajek, and A. Siemion, "Neural Network-Based Design of Two-Focal-Spot Terahertz Diffractive Optical Elements", IEEE Trans. Terahertz Sci. Technol. 14, 228 (2024). CrossRef M. Kaluza, P. Komorowski, M. Surma, A. Nieradka, P. Zagrajek, and A. Siemion, "Advanced diffractive optical elements implementing multiple-input spatial multiplexing of terahertz radiation", Opt. Lasers Eng. 184, 108606 (2025). CrossRef M. Surma, M. Kaluza, P. Komorowski, and A. Siemion, "Segmentation of THz holograms for homogenous illumination", Sci. Rep. 14, 12733 (2024). CrossRef Y. Luo, D. Mengu, N. T. Yardimci, Y. Rivenson, M. Veli, M. Jarrahi, and A. Ozcan, "Design of task-specific optical systems using broadband diffractive neural networks", Light Sci. Appl. 8, 112 (2019). CrossRef A. Siemion, "Terahertz Diffractive Optics—Smart Control over Radiation", J. Infrared Millim. Terahertz Waves 40, 477 (2019). CrossRef J. Suszek et al., "Evaluation of the shadow effect in terahertz kinoform gratings", Opt. Lett. 38, 1464 (2013). CrossRef H. Wang et al., "Two-photon polymerization lithography for imaging optics", Int. J. Extreme Manuf. 6, 042002 (2024). CrossRef H. Wang et al., "Bio-Inspired Semi-Active Safeguarding Design with Enhanced Impact Resistance via Shape Memory Effect", Adv. Funct. Mater. 33, 2214211 (2023). CrossRef O. Yermakov et al., "Fiber-based angular demultiplexer using nanoprinted periodic structures on single-mode multicore fibers", Nat. Commun. 16, 2294 (2025). CrossRef Z. Li et al., "Doughnut beam shaping based on a 3D nanoprinted microlens on fiber tip", Opt. Laser Technol. 167, 109798 (2023). CrossRef M. Kaluza, P. Komorowski, A. Nieradka, P. Zagrajek, and A. Siemion, "Implementing Terahertz Spatial Multiplexing and Frequency Demultiplexing Systems Using Diffractive Optical Elements for 6G Telecommunications Applications", IEEE Trans. Microw. Theory Techn. 73, 6037 (2025). CrossRef M. Sypek, "Light propagation in the Fresnel region. New numerical approach", Opt. Commun. 116, 43 (1995). CrossRef